1997
DOI: 10.1007/bf02765109
|View full text |Cite
|
Sign up to set email alerts
|

Differences in in vitro photodynamic sensitivity among head and neck cancers

Abstract: This study was conducted to address the question of how cancers of different histologies of the head and neck region responded to photodynamic therapy (PDT). Five human cancer cell lines were investigated: two squamous cell carcinoma lines (pharynx and tongue), mucoepidermoid carcinoma (submaxillary gland), rhabdomyosarcoma (embryonic) and adenocarcinoma (colon). The cell lines were treated with haematoporphyrin derivative (HpD) at doses of 0.78-25Mug ml(-1), with excitation of the absorbed drug by a 'black li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Each immunoglobulin was initially exposed to 2-mercaptoethanol that partially reduced disulphide bonds in the hinge area of the structure, [25][26][27] and then the raw material was isolated by size exclusion chromatography. Stannous ions in the form of Sn II -MDP were combined with the reduced immunoglobulin under an inert atmosphere, the stable complex proving to facilitate 99m Tc-pertechnetate reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Each immunoglobulin was initially exposed to 2-mercaptoethanol that partially reduced disulphide bonds in the hinge area of the structure, [25][26][27] and then the raw material was isolated by size exclusion chromatography. Stannous ions in the form of Sn II -MDP were combined with the reduced immunoglobulin under an inert atmosphere, the stable complex proving to facilitate 99m Tc-pertechnetate reduction.…”
Section: Discussionmentioning
confidence: 99%
“…9,33,35,37,40,46,48,52,55,66,67 Other porphyrin platform PSs such as PAD-S31, HpD, Photofrin II, Photosan III, hydroxy purpurin, mTHPP, and Protoporphyrin IX (PpIX) were studied in some articles. [56][57][58][59]62 Chlorophyll platform PSs, including chlorin e6, NPe6, chlorin p6, mTHPC, pheophorbide a, and 9-hydroxy pheophorbide a were applied in other studies . 29,31,38,39,41,43,49,54 One study used 15(1)-hydroxypurpurin-7-lactone ethyl methyl diester as a PS, which was isolated for the first time from an Araceae plant and referenced to Pha.…”
Section: Photosensitizermentioning
confidence: 99%
“…Overall assessment showed slightly better results reported in the third generation and new PSs. Some studies used only one concentration, 33,[38][39][40]43,45,[47][48][49]51,55,56,58,59,66,67 while others evaluated the effect of different concentrations on their cell lines. 9,23,[29][30][31][32]34,36,37,41,42,44,46,50,53,54,57,[60][61][62][63][64][65]68 Most studies showed that the results were dependent on concentrations.…”
Section: Photosensitizermentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work with PDT in SCCs suggests that it would be benefical in treatment of canine oral SCCs. A human pharyngeal SCC cell line has been shown to be one of the most sensitive cell types to PDT in vitro (Boonkitticharoen et al, 1997). Early-stage disease SCC of the head and neck treated with Photofrin resulted in 20 of 26 (77%) people achieving a complete response based on physical examination and histopathological confirmation.…”
Section: mentioning
confidence: 99%